2021
DOI: 10.3389/fnagi.2021.716068
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Body Mass Index and Intracranial Aneurysm Rupture: A Multicenter Retrospective Study

Abstract: Background and Aims: It has recently emerged the concept of “obesity paradox,” a term used to describe an inverse association between obesity and clinical outcomes in cardiovascular diseases and stroke. The purpose of this study was to investigate the association between body mass index (BMI) and the risk of intracranial aneurysm rupture.Methods: In this study, we conducted a retrospective analysis of a prospectively maintained database of patients with intracranial aneurysms from 21 medical centers in China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
(58 reference statements)
1
9
0
3
Order By: Relevance
“…They found that diabetes increased the risk for respiratory adverse events and death, hypertension increased the risk for cerebrovascular incidents, but that obesity was not associated with adverse outcomes. In a multicenter study, increased BMI appeared to have a protective effect on rupture in men over 50 years old [ 3 ]. However, in a review, it has also been concluded that the studies published so far could not provide convincing proof about this [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that diabetes increased the risk for respiratory adverse events and death, hypertension increased the risk for cerebrovascular incidents, but that obesity was not associated with adverse outcomes. In a multicenter study, increased BMI appeared to have a protective effect on rupture in men over 50 years old [ 3 ]. However, in a review, it has also been concluded that the studies published so far could not provide convincing proof about this [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the present findings, a study among UK women with approximately 2500 SAH events also demonstrated an inverse association of BMI with SAH . The biological mechanisms underpinning the inverse association between BMI and SAH are not fully understood and require further investigation . However, aneurysmal rupture, which accounts for approximately 85% of SAHs, has also demonstrated an inverse association with BMI …”
Section: Discussionmentioning
confidence: 99%
“…The biological mechanisms underpinning the inverse association between BMI and SAH are not fully understood and require further investigation . However, aneurysmal rupture, which accounts for approximately 85% of SAHs, has also demonstrated an inverse association with BMI …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that BMI tended to be lower in the ruptured group than in the unruptured group. In one study, increased BMI can be associated with lower aneurysm rupture risk [ 4 ]. However, in this study, in terms of BMI, the median value of BMI in this study was within the normal range (24.9 vs. 23.7), and neither groups were obese.…”
Section: Discussionmentioning
confidence: 99%